Edukasi Kesehatan Kulit melalui Pemanfaatan Sabun Belerang di Panti Asuhan Mamiyai : Pengabdian - Rifandi Perdana; Mandra Saragih; Tri Aprilianda Nura; Suci Febriany; Rumiris Situmorang; Jobrael Sitanggang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Skin health problems often occur in orphanages due to lack of awareness of hygiene and limited sanitation facilities. This service activity aims to improve the knowledge and skills of the children of Mamiyai Orphanage regarding skin health through education and training in making sulfur soap made from natural ingredients. The method used was a participatory approach, involving 38 participants in two sessions, namely education and soap making practice. Evaluation was conducted through pretest and posttest. Results showed a significant increase in average knowledge from 61.00 to 83.50 (p < 0.05). This finding is in line with Kolb's experiential learning theory that emphasizes the importance of direct experience in learning. In addition to improving understanding of skin care, the program equips participants with practical skills that can be developed as simple business opportunities. The integration of theoretical education and the practice of making sulfur soap proved effective in improving clean and healthy living behaviors in the orphanage environment.